Isolation, molecular characterization and extracellular enzymatic activity of culturable halophilic bacteria from hypersaline natural habitats - SUZAN AHMED BIN-SALMAN; REDA HASSAN AMASHA; SAMYAH D. JASTANIAH; MAGEDA M. ALY; KHALIL ALTAIF (Society for Indonesian Biodiversity, 2018)
Bin-Salman SA, Amasha RH, Jastaniah SD, Aly MM, Altaif K. 2018. Isolation, molecular characterization and extracellular enzymatic activity of culturable halophilic bacteria from hypersaline natural habitats. Biodiversitas 19: 1828-1834. Saline habitats, like the Dead Sea, are unusual extreme environments, due to their extreme salinity. Most saline habitats originate from the evaporation of seawater, and have a nearly neutral to slightly alkaline pH (such as the Red Sea (pH8.3) and Arabian Gulf, pH8.3). Ten halophilic bacterial strains (two Gram-negative) belonging to the family of Halomonadaceae and (eight Gram-positive), belonging to the family of Bacillaceae, were isolated from the Red Sea, Arabian Gulf, and Dead Sea by subjecting the isolates to a high salinity medium, followed by identification using 16S rRNA gene sequencing. Four of isolates were designated on the basis of their tolerance to high salinity; SBR1 exhibited 97% homology to Halomonas aquamarina, SBR2 showed 97% homology to Sediminibacillus sp., (Red Sea), SBA9 exhibited 94% homology to Halobacillus sp., (Arabian Gulf) and SBD17 gave 98% homology to Halobacillus dabanensis (Dead Sea). The isolates were also characterized by their physiological parameters, SBR1 showed optimum growth at 30°C, pH8.5 and1.5M NaCl, SBR2 at 30°C, pH6.0 and 1M NaCl. Optimum conditions for SBA9 were 35°C, pH6.5 and 1M NaCl and for SBD17, 37°C, pH7.0 and 1M NaCl.